Studi Literatur: 7 Kebiasaan Anak Indonesia Hebat dalam Pembelajaran Matematika - A’yunina, Quurotul; Khoiri, Miftakhul; Habibah, Yuhanidz Nur; Zahirah, Inneke Najmah; Fuat, Fuat (Indo-MathEdu Intellectuals Journal, 2025)
The background of this research is that education is a crucial element in building a great, intelligent, and noble golden generation of Indonesia towards the vision of Indonesia 2045. This study aims to analyze the concept of mathematics learning through the implementation of the 7 habits of great Indonesian children, namely the habit of waking up early, praying, exercising, eating healthy and nutritious food, loving to learn, being in society, and sleeping early. This type of research uses the Systematic Literature Review method or also known as SLR. In this study, the researcher used a data collection study by reading, taking notes, reviewing literature or reading materials that were selected and considered appropriate to the main topic of the study "Implementation of 7 Habits of Great Indonesian Children in Mathematics Learning that can have a positive impact on students' attitudes, motivation, and learning outcomes. The readings chosen by the researcher were around the period 2015-2025. The results of the study of the relationship between each habit and mathematics learning are being responsible (Be Proactive), starting with the end goal (Begin with the End in Mind), putting the main thing first (Put First Things First), thinking win-win (Think Win-Win), trying to understand first, then be understood (Seek First to Understand, Then to Be Understood), synergy (Synergize), sharpening the saw (Sharpen the Saw)